2013
DOI: 10.1186/1423-0127-20-54
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-rich domain of scavenger receptor AI modulates the efficacy of surface targeting and mediates oligomeric Aβ internalization

Abstract: BackgroundInsufficient clearance of soluble oligomeric amyloid-β peptide (oAβ) in the central nervous system leads to the synaptic and memory deficits in Alzheimer's disease (AD). Previously we have identified scavenger receptor class A (SR-A) of microglia mediates oligomeric amyloid-β peptide (oAβ) internalization by siRNA approach. SR-A is a member of cysteine-rich domain (SRCR) superfamily which contains proteins actively modulating the innate immunity and host defense, however the functions of the SRCR dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…5 Others have reported similar findings when expressing artificial constructs of SRA. 19 We have demonstrated that MARCO and MARCOII are expressed at comparable levels in our transient transfection system by western blotting and that they both expressed on the cell surface by flow cytometry (Figures 2a and b) and IF microscopy (Figures 2c-j). Therefore, differences in function are not due to differences in protein expression.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…5 Others have reported similar findings when expressing artificial constructs of SRA. 19 We have demonstrated that MARCO and MARCOII are expressed at comparable levels in our transient transfection system by western blotting and that they both expressed on the cell surface by flow cytometry (Figures 2a and b) and IF microscopy (Figures 2c-j). Therefore, differences in function are not due to differences in protein expression.…”
Section: Discussionmentioning
confidence: 61%
“…Previous work by Brännström et al 5 highlighted the importance of the RxR motif within the SRCR domain of MARCO for ligand binding using artificially truncated or mutated constructs; however, some constructs were not expressed on the cell surface 5 . Others have reported similar findings when expressing artificial constructs of SRA 19 . We have demonstrated that MARCO and MARCOII are expressed at comparable levels in our transient transfection system by western blotting and that they both expressed on the cell surface by flow cytometry (Figures 2a and b) and IF microscopy (Figures 2c and j).…”
Section: Discussionmentioning
confidence: 93%
“…18 Recently the cysteine rich domain of SRA was shown to also serve as a potential binding site for Ac-LDL. 20 We recently completed the construction of SRA cysteine rich domain homology models 18 based on the available crystal structures of the cysteine rich domain of MARCO, another member of class A scavenger receptor family, in its monomeric and dimeric form (PDB: 2OY3 and 2OYA). 21 Mouse scavenger receptor MARCO had the highest sequence identity (43%) and homology (63%) to SRA and the fact that both proteins belong to the same receptor family, made the crystal structure of MARCO a suitable choice as the template for homology modeling.…”
Section: Resultsmentioning
confidence: 99%
“…Activated scavenger receptor A (SR-A) promotes glial internalization of Amyloid-β peptide (Aβ), which is a key histopathological characteristic of Alzheimer’s disease (AD) [ 1 , 2 ]. Previously, we identified SR-A as the prominent subtype of scavenger receptor mediating oligomeric Aβ (oAβ) internalization in microglia, and revealed that the cysteine-rich (SRCR) domain of SR-A type I (SR-AI) may be the critical domain on modulating the efficacy of surface targeting and mediating oAβ internalization [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%